The dubious pranks of Shaindy Goodman - Lowe, Mari (Levine Querido, 2023)
Helping her popular next-door neighbor Gayil set up what she thinks are harmless pranks, 12-year-old Orthodox Jewish girl Shaindy must figure out how to stop them before she becomes the next target when the pranks escalate and turn malicious.